Effect of a didactic proposal in knowledge, attitudes and practices in a group of diabetic seniors - Clarke Spence, Inés (2005)
This article describes the effect of a didactic proposal about self care towards the knowledge, attitudes and practices of a group of elderly diabetics participants of an experimental investigation that was also completed with a qualitative technique method. The results revealed a positive effect of the educational proposal, when the participants in the teaching-learning process showed an increase in their knowledge about the desease, better attitude towards the desease and treatment, as well as developments of healthy lifestyles that favor the adherence to the treatment. These results showed to be statistically significant, when comparing the results of the evaluations that were applied to the groups before and after the educational process.